BIOLOGICAL PROPERTIES OF PSEUDOMONAS AERUGINOSA GROWN IN DIFFERENT ARTIFICIAL NUTRITIONAL MEDIA - Gorodnytska, N.I.; Martynov, A.V.; Osolodchenko, T.P. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
In this article the results of study of biological properties of Pseudomonas aeruginosa № 66-16 vaccine strains, that was cultivated in different artificial nutritional media were presented. It was shown, that mediums from industrial waste don’t differ from standart ones by Pseudomonas aeruginosa strains properties, that cultivated on.